Treating emerging contaminants (pharmaceuticals) in wastewater and drinking water treatment plants - Barceló D.; Petrovic M.; Radjenovic J. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
In this study the behaviour of several pharmaceuticals belonging to different therapeutic categories (analgesics and anti-inflammatory drugs, lipid regulators, antibiotics, etc.) was monitored during the treatment of wastewater in a laboratory-scale membrane bioreactor (MBR) and in a full-scale drinking water treatment plant (DWTP) using reverse osmosis (RO) and nanofiltration (NF). The results of MBR were compared with the removal of the target compounds in a conventional activated sludge (CAS) process in an existing wastewater treatment facility. The performance of an MBR was monitored during approximately two months in order to investigate a long-term operational stability of the system and a possible influence of solid retention time on the removal efficiencies of target compounds. The behaviour of the selected pharmaceutical residues facing an NF/RO membrane and evaluation of the performance of this kind of advanced treatment was studied under real conditions of a full-scale DWTP. Excellent overall performance of both NF and RO was noted, with high rejection percentages for almost all of the pharmaceutical residues investigated (>85 percent), while in wastewater treatment using an MBR the pharmaceutical compounds were generally removed to a higher extent than during CAS process.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)